A comparison of Australian and French families affected by sarcoma: perceptions of genetics and incidental findings. (January 2018) - Rasmussen, Victoria; Forrest, Laura E; Rogasik, Muriel; Girodet, Magali; Meeus, Pierre; Sunyach, Marie-Pierre; Blay, Jean-Yves; Bally, Olivia; Brahmi, Mehdi; Ballinger, Mandy L; Niedermayr, Eveline; Thomas, David M; et al.
Aim: To compare Australian and French perceptions of genetics and preferences regarding the return of incidental findings.Methods: Participants from the International Sarcoma Kindred Study received a survey at intake to cancer referral units. A total of 1442 Australian and 479 French individuals affected by sarcoma and their unaffected family members responded to four hypothetical scenarios depicting hereditary conditions of varying treatability and severity.Results: Australians' preference for the return of incidental findings was consistently higher than French for all scenarios. Country group differences were significant for two scenarios when individual characteristics were controlled through multivariable analyses.Conclusion: Findings support the need for guidelines that are sensitive to sociocultural context and promote autonomous decision-making.